2011
DOI: 10.1111/j.1365-2133.2011.10318.x
|View full text |Cite
|
Sign up to set email alerts
|

Contagious itch in humans: a study of visual ‘transmission’ of itch in atopic dermatitis and healthy subjects

Abstract: Anecdotal evidence suggests “contagious” itch occurs in daily life when we see other people itch and scratch. This phenomenon has not been systematically studied previously, and factors which can amplify itch perception were unknown. We investigated whether exposure to visual cues of itch can induce or intensify itch in healthy and atopic dermatitis subjects. Participants received histamine or a saline control delivered to the forearm and were asked to watch short video clips of people scratching. Spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
124
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(146 citation statements)
references
References 9 publications
14
124
2
2
Order By: Relevance
“…Although no previous study has examined the neural correlates of visually induced itch, several researchers have suggested that the "mirror neuron system" may be essential for contagious itching (2,4). Mirror neurons, first reported in the macaque brain, respond to both a self-executed action and the sight of an action performed by another person (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although no previous study has examined the neural correlates of visually induced itch, several researchers have suggested that the "mirror neuron system" may be essential for contagious itching (2,4). Mirror neurons, first reported in the macaque brain, respond to both a self-executed action and the sight of an action performed by another person (15).…”
mentioning
confidence: 99%
“…Subjective feelings of itchiness and observable increases in scratching can be evoked by watching someone scratch himself or by listening to a lecture on dermatologic conditions (1,2). Although many aspects of the neurobiology of itch are now appreciated (3,4), the standard definition of itch ("an unpleasant sensation associated with an urge to scratch") and its description as a symptom within clinical disorders remain essentially subjective and based on self-report.…”
mentioning
confidence: 99%
“…Although recent studies have shown sexspecific differences in the quality, localization and triggering of chronic pruritus, and in the underlying disease and scratching behavior [6] , studies from the experimental literature have typically found no sex differences in itch contagion [3] , itch ratings or scratch behavior [1] . However, this may be due to limited sample sizes (eg, only 3 males and 8 females with AD were tested in Papoiu et al [1] ) or biased samples that recruited twice as many females to males [3] . To address this bias, similar numbers of males and females were recruited in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…One factor that could influence susceptibility to VEI is having a history of pruritic skin conditions (PSCs). Previous studies have demonstrated that a combination of watching videos of people scratching while participants received either histamine or saline administration caused self-reported itch intensity to increase in all participants, but resulted in a doubling of spontaneous scratching episodes in those with AD who also appeared to scratch a more widespread area for longer [1] . Lloyd et al [5] have shown that images containing itch-related stimuli in contact with the body (such as ants crawling on the skin) produce the highest ratings of itch intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation